Inovasi Alat Otomatisasi Packing Produksi Temulawak untuk Meningkatkan Efisiensi dan Kapasitas di UMKM Sekar Temulawak - Annisa Maulidia Damayanti; Dinda Ayu Permatasari; Donny Radianto; Qonitatul Hasanah; Rendi Pambudi Wicaksono; Zakiyah Amalia (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
In an effort to enhance production efficiency and digital marketing at UMKM Sekar Temulawak, an innovation was introduced in the form of an automatic filtering and packaging machine alongside the application of digital marketing strategies. The machine was designed based on the partner's specific needs and tested on a limited scale, resulting in a 40% increase in packaging efficiency. Additionally, the research team collaborated with the partner to develop a website for digital marketing, which has been registered for Intellectual Property Rights (IPR). A Focus Group Discussion (FGD) was conducted to prepare the machine and draft the usage procedures and digital marketing strategy. This project provides a technology-based solution to help UMKM expand their market reach